O sentido e o significado do corpo próprio do profissional de saúde ao cuidar do outro que está morrendo : uma abordagem à luz de Merleau-Ponty - Santana, Maria Teresa Brito Mariotti de (2005)
In this study, it is intended to understand the proper body of the health professional when taking care of the other one who is dying. Its goal was to grasp the senses and the meaning of the proper body of the health professional in the process of caring/taking care of the other proper body who is dying within the hospital context. To build intimacy room in the hospital to hear the testimonies of the health professionals about their experiences in taking care of the other one who is dying. To reach that, it was chosen to use a qualitative approach, within the existential phenomenology, which includes the understanding and the interpretation of the meaning, considering the subject as a historical-cultural being who captures the senses and the meaning of the perceived world. It was carried out interviews with ten professionals defined as subjects of study. The interviews presented mainly the following questions: How did you decide to take care of the terminal patients? How do you perceive your body when you take care of terminal patients? After the transcriptions, the testimonies were individually analyzed rescuing these themes: Perceptive Conscience of the body, the place the body occupies in the world, limits of the existence in the body. The analysis aim was the hermeneutical reflection about the phenomenon, grasping the senses and the meaning: the proper body of the health professional in a perspective of this very body as conscience, that continually needs to be taken care of. Therefore, there is a body that directs itself embodied the world, to another elected figures in the funds, before the possibilities that the medium offers and positions that the body takes on this. When the body becomes the "point of view of the world" rather than an object, the structure of space-time existence is reawakened perceptual and objective thinking is usually deleted. There is a conscious intentional restructuring that enabled the development of technology for interdisciplinary care of the body as consciousness by the dynamics of the senses, using the existential phenomenological method in the light of Merleau-Ponty.